2007
DOI: 10.1590/s0100-54052007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de um vírus baciliforme isolado de Solanum violaefolium transmitido pelos ácaros Brevipalpus phoenicis e Brevipalpus obovatus (Acari: Tenuipalpidae)

Abstract: Solanum violaefolium is an ornamental plant, with prostrate, trailing growth habit and is cultivated in shaded areas. A virus that causes ringspot symptoms on its leaves, tentatively named as Solanum violaefolium ringspot virus (SvRSV) and transmitted by Brevipalpus phoenicis (Acari: Tenuipalpidae) was found in Piracicaba city, São Paulo State. It is a bacilliform virus that resembles other cytoplasmic viruses transmitted by Brevipalpus sp. The objective of this work is to describe the biological properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 7 publications
4
13
0
9
Order By: Relevance
“…Negative-positive thresholds were set at two times the mean of healthy control sample absorbance. Additionally to sweet oranges, plants infected by other cytoplasmic type of Brevipalpus-transmitted viruses (BrTV-C) were also tested to verify the possibility of cross-reaction: Solanum violaefolium Schott./Solanum violaefolium ringspot virus (SvRSV), from Piracicaba, SP (Ferreira et al, 2007), Hibiscus rosa-sinensis L./Hibiscus green spot virus (HibGSV) from Piracicaba, SP (Kitajima et al, 2010), Ligustrum lucidum W.T. Aiton and Ligustrum sinensis Lour./Ligustrum ringspot virus (LigRSV) from Piracicaba, SP (Vergani, 1942;Kitajima et al, 2010), Passiflora edulis Sims.…”
Section: Pta-elisa (Plate Trapped Antigen -Enzyme Linked Immunosorbenmentioning
confidence: 99%
“…Negative-positive thresholds were set at two times the mean of healthy control sample absorbance. Additionally to sweet oranges, plants infected by other cytoplasmic type of Brevipalpus-transmitted viruses (BrTV-C) were also tested to verify the possibility of cross-reaction: Solanum violaefolium Schott./Solanum violaefolium ringspot virus (SvRSV), from Piracicaba, SP (Ferreira et al, 2007), Hibiscus rosa-sinensis L./Hibiscus green spot virus (HibGSV) from Piracicaba, SP (Kitajima et al, 2010), Ligustrum lucidum W.T. Aiton and Ligustrum sinensis Lour./Ligustrum ringspot virus (LigRSV) from Piracicaba, SP (Vergani, 1942;Kitajima et al, 2010), Passiflora edulis Sims.…”
Section: Pta-elisa (Plate Trapped Antigen -Enzyme Linked Immunosorbenmentioning
confidence: 99%
“…O objetivo deste trabalho foi verificar como os tecidos das diferentes plantas hospedeiras reagem à infecção pelo ClCSV a fim de complementar a caracterização deste vírus e comparar estas alterações histológicas com aquelas causadas por outros vírus transmitidas por Brevipalpus (2,7,16,19,20).…”
Section: Introductionunclassified
“…On the other hand, the genome of CiLV-C showed that this is not a rhabdovirus, and it was recently accepted as the type member of the genus Cilevirus (Carstens 2010). In the work of Ferreira et al (2007), some fragments of the genome of Solanum violaefolium ringspot virus (SvRSV) showed similarities with CiLV-C, but whether or not it belongs to the Cilevirus needs to be proven. These atypical plant viruses induce chlorotic or necrotic local lesions on leaves, stems and fruits of their hosts ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are unspecific, can be unreliable and, regarding TEM, are expensive and time demanding. During the last decade, some BrTVs were partially sequenced and, consequently, molecular-based tools were developed for their detection in planta (Blanchfield et al 2001;Locali et al 2003;Ferreira et al 2007;Kubo et al 2009). The first study on the molecular detection of BrTVs in their mite vectors is the preliminary report of Locali et al (2003), who were able to detect Citrus leprosis virus C (CiLV-C) by RT-PCR in samples of 400 viruliferous mites.…”
Section: Introductionmentioning
confidence: 99%